PREVALENSI DEFISIENSI GLUCOSE-6-PHOSPHATE DEHYDROGENASE (G6PD) PADA ANAK SEKOLAH DASAR YANG TINGGAL DI DAERAH ENDEMIS MALARIA DI SULAWESI UTARA - S.B Tuda, Josef; J. Kepel, Billy; Nakatsu, Masami; Matsuoka, Hiroyuki (Jurnal Kedokteran YARSI, 2007)
Deficiency of glucose-6-phosphate dehydrogenase (G6PD) is the most common enzyme disorder in the world with a very high incidence in the tropics and sub-tropics as a result of malaria selection. North Sulawesi is a part of Indonesian archipelago where malaria has been endemic. This study was aimed to examine the prevalence of G6PD deficiency in the region. An observational cross sectional study was conducted on primary school students belong to different ethnic groups. The purposive sampling method was used to select 442 study subjects, age 5-9 years. The G6PDdeficiency screening test was carried out using G6PD-assay kit. The prevalences of G6PDdeficiency male students were 0% in the Minahasans, 7,4%-12,0% in the Sangihenese, and 4,0%10,3% in the Bolaang Mongondownese. The results suggest that the highest prevalence of G6PD deficiency was in the Sangihe ethnic group. Further molecular analysis would be beneficial to study the genetic relationship of those populations with other neighboring population.